Perancangan Sistem Informasi Presensi Non Pegawai Berbasis Mobile Menggunakan QR Code di PT Perkebunan Nusantara IV Medan - Maulana, Dimas Krisna; Samsudin, Samsudin (Teknik Informatika Fakultas Ilmu Komputer, 2024)
The management of non-employee attendance is a crucial element in building an inclusive and equitable work environment at PT. Nusantara IV Plantation Medan. This study identifies inequality in the existing attendance system, where employees still have a separate and efficient attendance system, this study proposes the design of an Attendance Information System that focuses on fairness and recognition of non-employee attendance. The purpose of this study is to design a system that allows non-employees to have the same attendance access as permanent employees, which can be done through a mobile application using QR-Code technology. The data collection method is carried out through interviews and field observations as well as literature studies, while the development of the system uses the waterfall method. Through this approach, it is hoped that equality will be created in treating the presence of non-employees so that they are also valued and recognized like other permanent employees.